Public opinion, transatlantic relations and the use of force - Everts, Philip P. 1938-; Isernia, Pierangelo (Palgrave Macmillan, 2015)
"This book examines the evidence for the theory that there are fundamental differences between American and European public attitudes about the acceptability of military force. Philip Everts and Pierangelo Isernia show that Americans and Europeans share similar attitudes on international affairs but do indeed differ considerably on the issue of military force. This became evident in a number of recent cases of international conflict and military interventions, such as the war over Kosovo just before the millennium, as well as the military actions in the fight against international terrorism in Afghanistan and Iraq. Using new data Everts and Isernia chart and explain these attitudes and their determinants. Public Opinion, Transatlantic Relations and the Use of Force takes a deliberately comparative and transatlantic perspective in exploring the sources of these differences and in discussing the political implications of the transatlantic gap on the use of force, as well as in its assessment of the conditions under which it could be bridged or might be aggravated"..
Keywords: Europäische Union; POLITICAL SCIENCE / Government / Comparative; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Globalization; SOCIAL SCIENCE / Violence in Society; Außenpolitik; Globalisierung; War -- Public opinion; War and society -- European Union countries; War and society -- United States; Bewaffneter Konflikt; Militärische Intervention; Öffentliche Meinung; Politische Entscheidung; Europäische Union. Mitgliedsstaaten; USA; European Union countries -- Military policy -- Public opinion; United States -- Military policy -- Public opinion; European Union countries -- Public opinion; United States -- Public opinion; European Union countries -- Foreign relations -- United States; United States -- Foreign relations -- European Union countries